Eco-Theology and the Future of Earth - Abdul Fatah (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
The concept of eco-theology is a form of constructive theology formula that examines the interrelation between religion and nature, especially in dealing with the problems of the environment. Environmental problems caused by human hands, such as : landslides, floods, drought, pollution and etc are evidence that our environment is really in critical condition. Therefore, as human who directly interacts with environment has moral responsibility to preserve and maintain environmental quality. Human is center and the base of the entire environmental damage. And it happened because the patterns of human behavior itself is not sensitive to the environment, therefore, to solve environmental problems not only make regulation and sanctions but also develop the mental character leads to morality as the foundation to look at nature as an integral part of the human. Religion is the answer to open its followers’ awareness to the importance of protecting the environment, through the mechanism of religious texts reading (exegesis). Eco-theology is containing universal principles in maintaining and caring the earth. In Eco-theology there are spiritual dimension, faith, worldview, ethics, morality and religion, their combination is hoped able to drive a more understanding to human beings about how he should locate the position in the universe related to his interaction with environment and other creatures, by this future of earth will be better.   Keywords : Eco-Theology, Environment, Nature and Human